A review of aerosol optical properties in selective parts of Nepal - Adhikari, Sudip; Regmi, Jeevan (Himalayan Physics, 2025)
Aerosols, tiny solid or liquid particles suspended in the air, influence the Earth’s climate, radiative budget, human health, and air quality by absorbing and scattering the solar radiation. It makes the study of aerosol properties and behavior highly demanding in the present context. Since the aerosol concentration and chemical make-up possess a high level of uncertainty with time and space, continuous observation and monitoring can provide some insight into their microphysical properties. In this regard, this review is based on research articles on aerosol optical depth (AOD) and itsoptical properties published between 2000 and 2024, covering various parts of Nepal and its immediate periphery. It covers most articles based on AERONET data, validated with satellite data, and a few articles using surface data from low-cost sensors. It is found that AOD shows spectral variation. It decreases with increasing wavelength, showing a strongdependence at shorter wavelengths. This result aligns with findings from various parts of the world. It also shows significant seasonal and geographical variations, with distinct patterns. It means that local environmental factors and anthropogenic activities greatly influence AOD. The review of AE over Nepal shows a predominance of fine modeparticles during the post-monsoon season. But, during the remaining seasons, both the fine and coarse mode particles are present in almost all places.